2005
DOI: 10.1210/jc.2004-1306
|View full text |Cite
|
Sign up to set email alerts
|

Lean Body Mass Is a Major Determinant of Levothyroxine Dosage in the Treatment of Thyroid Diseases

Abstract: Total body weight is usually employed to calculate the amount of l-T(4) to be administered in patients with thyroid diseases. The aim of this study was to evaluate the effect of body composition on l-T(4) requirements. Body composition was assessed by dual energy x-ray absorptiometry in 75 patients on TSH-suppressive l-T(4) therapy after conventional thyroid ablation for differentiated cancer. The mean daily dose of l-T(4) was lower in normal-weight (127.5 +/- 21.3 mug/d) vs. overweight (139.4 +/- 24.5) and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(144 citation statements)
references
References 28 publications
2
132
1
9
Order By: Relevance
“…This is in contrast with most studies, showing low/normal levels of FT 4 in obese subjects. As an alternative explanation, it should be considered that the turnover rate of T 4 is proportional to body size (73) that is indeed a main determinant of the substitution dose of levothyroxine (L-T 4 ) in hypothyroid subjects (74,75). Thus, an increased rate of thyroid hormone disposal (resulting from a large body size) would be the causative event promoting an activation of the hypothalamus-pituitary-thyroid axis aimed at maintaining serum thyroid hormones within the euthyroid range.…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 99%
“…This is in contrast with most studies, showing low/normal levels of FT 4 in obese subjects. As an alternative explanation, it should be considered that the turnover rate of T 4 is proportional to body size (73) that is indeed a main determinant of the substitution dose of levothyroxine (L-T 4 ) in hypothyroid subjects (74,75). Thus, an increased rate of thyroid hormone disposal (resulting from a large body size) would be the causative event promoting an activation of the hypothalamus-pituitary-thyroid axis aimed at maintaining serum thyroid hormones within the euthyroid range.…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 99%
“…These estimates include 1.6 mg (1-8), 1.7 mg (4,6), 1.8 mg (5,9), 2.0 mg (9), and 2.1 mg (5) LT 4 per kilogram actual BW. LT 4 replacement doses in thyroid cancer patients requiring TSH suppression are generally higher and on the order of 2.0-2.56 mg/kg (1,5,6). A study by Santini et al showed that ideal BW (IBW) is a better predictor of LT 4 dose than actual BW and that any gender differences in LT 4 dose requirement were accounted for by lean body mass (5).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, only two patients out of 23 showed FT 3 values below normal and none showed subnormal FT 4 . Since T 4 metabolism is slowed down in elderly patients (12) and the dose of T 4 should be accordingly reduced, age may represent a confounding factor. So far, patients were subdivided into two agerelated groups: under 50 years of age (nZ11) and 50 years of age or older (nZ12) and the pre-and post-surgical dose has been compared accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…The individually tailored dose is the dose of T 4 which is administered following a standardized assumption procedure and titrated on the basis of patient's age, weight, BMI, the amount of residual thyroid tissue and the ability to absorb the hormone (12,14,15,21,22,23,24). All patients were treated with the same brand of oral and agreed to take T 4 under fasting conditions, abstaining from eating or drinking anything other than water for at least 1 h after treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation